The Frequency of Hepatitis Virus Infection Markers Among Highly Qualified Sportsmen - L. Yu. Ilchenko; I. A. Morozov; T. V. Kozhanova; N. V. Soboleva; L. I. Melnikova; I. V. Kruglova (SINAPS LLC, 2020)
Study Objective is to evaluate prevalence of hepatitis A, B, C, E, and TT virus infection markers in highly qualified sportsmen. Study Design: multicenter open single-site clinical study.Materials and Methods: 100 blood serum samples of sportsmen (game, complex coordination, technical, etc.) were studied. Biological material (blood serum) was obtained from 54 men and 46 women aged 16 to 45 years during an in-depth medical examination. All sportsmen filled out a questionnaire, including demographic data, description of the sport, information about infection risk factors, information about the presence of acute viral hepatitis and vaccination. Anti-HAV IgG, HBsAg, anti-HBcore, anti-HCV, anti-HEV IgG, anti-HEV IgM were determined in the blood serum by enzyme immunoassay; using polymerase chain reaction - DNA Anelloviridae (TTV, TTMDV, TTMV). Study Results: Anti-HAV IgG was detected in 57/66 (86,4%) sportsmen, women (91,2%) predominated, among them a third were engaged in synchronized swimming. 7/57 (12,3%) of the examined had indications of vaccination against hepatitis A. The frequency of anti-HEV IgG did not exceed 3% (2/66). anti-HEV IgM were not detected in any case. Also, none of the examined sportsmen in the blood serum was not determined HBsAg. However, anti-HBcore (marker of latent HBV infection) was detected in 13% (13/100) of the samples. The detection rate of anti-HCV was low, combined with the presence of anti-HBcore was 2% (2/100). In addition, DNA TTV, TTMDV and TTMV, respectively, were found in serum samples from 66/100 (86%), 79/100 (79%), 71/100 of sportsmen. Conclusion: The high frequency of hepatitis virus markers was found (HAV - 74,1%, TTV/TTMDV /TTMV - 71-86%), HBV - 13%, HEV - 3%, HCV - 2%). All patients denied a history of acute viral hepatitis. Vaccination against hepatitis A and B is a modern strategy that prevents infection and the development of acute viral hepatitis. Its mandatory holding should become part of the targeted preparation of sportsmen to achieve the highest sports results.